Diabetes Patients Perceptions on Drugs Consultation Program by Pharmacists - Budi Sumaryono; Moelyono Moektiwardoyo; Ari Yulianto (Pharmacology and Clinical Pharmacy Research)
Drugs consultation by pharmacist is an important service to improve the quality of medication use in patients with type 2 diabetes mellitus (T2DM). Perception of patients regarding this service is very useful to boost pharmacists confidence to conduct such service. The purpose of this study is to provide an overview regarding interests and categories of drugs consultation needed by T2DM patients and to determine the effect of quality of drugs consultation on patients interest to participate in such program. Survey and interviews were conducted with T2DM patients in outpatient clinic, Dr. M. Salamun Air Force Hospital, Bandung during April-June 2013. One hundred patients were recruited for this study. Most of the patients consumed combination of oral antidiabetic and non-antidiabetic medication (71 %) and were given polypharmacy (45 %). The results showed that the information regarding drugs interactions, adverse drugs reaction (ADR), and drugs dosage were among the aspects that should be included in drugs consultation service by pharmacists. The quality of drug information service was associated with increased interest to participate in such program. These aspects should be considered in the implementation of drugs consultation program by pharmacists.Keywords: drugs consultation, T2DM, pharmacists